Phytochemical analysis, Antimicrobial, insecticidal and antiradical activity of Hydnocarpus pentandra (Buch.-Ham.) Oken - Prashith Kekuda TR; Dunkana Negussa Kenie; Chetan DM; Raghavendra L Hallur (International Journal of Phytomedicine, 2017)
Objectives: The present study was conducted to evaluate antimicrobial, insecticidal and radical scavenging activity of leaf extract of Hydnocarpus pentandra (Buch.-Ham.) Oken belonging to the family Achariaceae. Methods: Extraction process of shade dried and powdered leaf was carried out by maceration technique. Extract was screened for phytochemicals by standard tests. Antibacterial and antifungal activity of leaf extract was determined by Agar well diffusion and Poisoned food technique respectively. Antiradical activity of leaf extract was evaluated by two in vitro assays namely 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azinobis 3-ethylbenzothiazoline 6-sulfonate (ABTS) free radical scavenging assays. Insecticidal activity of leaf extract was determined against II instar and IV instar larvae of Aedes aegypti. Results: Preliminary phytochemical analysis showed the presence of alkaloids, flavonoids, tannins, saponins, glycosides, triterpenes and steroids in the leaf extract. Leaf extract exhibited marked inhibitory activity against Gram positive bacteria when compared to Gram negative bacteria. Bacillus cereus (zone of inhibition 1.86±0.05cm) and Escherichia coli (zone of inhibition 1.06±0.05cm) were inhibited to highest and least extent respectively. Extract was effective in inhibiting mycelial growth of seed-borne fungi. Among fungi, the susceptibility to extract was in the order: Curvularia sp. (53.64% inhibition) > Fusarium sp. (45.81% inhibition) > Alternaria sp. (35.08% inhibition). The extract exhibited concentration dependent larvicidal activity with marked activity being observed against II instar larvae (LC50 value 0.79mg/ml) when compared to IV instar larvae (LC50 value 1.37mg/ml). Leaf extract scavenged DPPH and ABTS radicals dose dependently with an IC50 value of 13.91µg/ml and 6.03µg/ml respectively. Conclusions: The plant is shown to be an important source of bioactive agents. The observed bioactivities could be attributed to the phytochemicals present in the leaf extract. Further studies on characterization and bioactivity determination of isolated components from leaf extract are to be carried out.